If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2n = n + 15 Reorder the terms: 2 + -2n = 15 + n Solving 2 + -2n = 15 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 2 + -2n + -1n = 15 + n + -1n Combine like terms: -2n + -1n = -3n 2 + -3n = 15 + n + -1n Combine like terms: n + -1n = 0 2 + -3n = 15 + 0 2 + -3n = 15 Add '-2' to each side of the equation. 2 + -2 + -3n = 15 + -2 Combine like terms: 2 + -2 = 0 0 + -3n = 15 + -2 -3n = 15 + -2 Combine like terms: 15 + -2 = 13 -3n = 13 Divide each side by '-3'. n = -4.333333333 Simplifying n = -4.333333333
| -20=10-6+n | | -16=5+n | | 6(3-2z)+13z-4= | | 4+3n=1-4n | | 36+p-4=p | | 3x-9=x+4 | | v(v+1)=272 | | 2-8v=2v+8 | | =6x^2+5xy-25y^2 | | 5m+1=3m+9 | | v(v+1)=132 | | 4t+20=15 | | 5p=1-21 | | 3n=6+15 | | -13j(4j-32)=507 | | -n-3n= | | 35k^2-22k-3=0 | | 7k^2-6k+3=0 | | .3x^2=1.2x+.3 | | 11y-31=90 | | 4x^2+600x-4000=0 | | 100x=7234.56(75) | | 3n^2-6n-45=0 | | 2304(3.14)=X | | 12b^2+17b+6=0 | | 2m^2+13m-24=0 | | 13-6f=31 | | 2(x+17)=400 | | n^2+23=0 | | 3c^2-10=13c | | 2x^2-16x+15=0 | | 2x^2+16x+15=0 |